Sweet potato and potato residual flours as potential nutritional and healthy food material - Dong JU; Tai-hua MU; Hong-nan SUN (Journal of Integrative Agriculture, 2017)
In this study, the proximate composition, mineral content and amino acid composition of starch processing residues from 10 cultivars of sweet potato and 10 cultivars of potato were determined, and the nutritional and health-related values of these residues were investigated. The residual flours contained 20.63–31.48 g and 17.14–28.57 g rich dietary fiber per 100 g dry weight for sweet potato and potato, respectively, as well as mineral elements, including potassium, ferrum, zinc and copper. The highest limiting amino acid score (AAS) of the almost balanced amino acid composition were observed to be 71.07 and 57.96 for sweet potato and potato residues, respectively. A grey relational analysis showed that the nutritional values of Jishu 4 at 0.7519 and LT-5 at 0.7281 were the highest among the sweet potato and potato residues, respectively. The evaluation of the sweet potato/potato residues, the by-products of the starch industry, based on recommended daily intake (RDI) standards, indicated that the residues have potential nutritional and health-related food values.